Learning Organization dan Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Kantor Cabang BNI 46 Malang) - Rofiati Rofiati; Ainur Rofiq; Dwita Ayu Ilmania (STIE Malangkucecwara, 2015)
This research investigates the influence of transformational leadership and organizational culture on organizational performance, either directly or indirectly through learning organization and employee work satisfaction at the Malang Branch Office of BNI 46. Research method is quantitative. Sample includes 126 regular employees. Sampling techniques are proportional random sampling and simple random sampling. Data analysis method is Partial Least Square. Research indicates that transformational leadership and organizational culture have positive impact on organizational performance, by direct way or indirect manner, through learning organization and employee work satisfaction. It is also found that organizational culture has the greatest impact on learning organization, employee work satisfaction, and organizational performance if compared to transformational leadership.